Overexpression analysis of plant transcription factors - Zhang, J.Z.
Transcription factors (TFs)play important roles in plant development and its response to the environment. A variety of reverse genetics tools have been developed to study TF function, the two most commonly used ones being knockout and overexpression. Because of the unique characteristics and modes of action of TFs, the overexpression strategy has been particularly effective in revealing TF function. Thus, a number of overexpression-based methodologies - constitutive expression, tissue-specific expression, chemically inducible expression and overexpression of modified TFs - have been developed and are used in the analysis of TF function.